Exposing the benefits of micro-organisms to human beings for High School students in São Luís-MA (Research, Society and Development, 2021)
Dealing with microorganisms and relating them to their extensive range of benefits, in the school environment, is of paramount importance in the perspective of putting aside the concept that they are only harmful to human health. The aim of the project was to find out what high school students understand or believe they understand about microorganisms, and from that, promote knowledge and undo distorted concepts, ensuring that microorganisms are also likely to benefit. The project was carried out at the Colégio Marista Araçagy public school located in the municipality of São José de Ribamar, in Maranhão, with students from the 3° year of high school. Previously, the students were pre-evaluated so that we could estimate their knowledge about microorganisms and how beneficial they are. Soon after, the theme was approached with the help of slides, where concepts, benefits and examples were reported. Then, a questionnaire was applied again in order to measure the performance and learning after subjecting them to the proposed action. After analyzing the questionnaire, it was found that of the 31 students who participated, 39% had no knowledge about the topic, while 61% said they had already had contact with the topic and 10% of the students said that all bacteria are pathogenic. It was only possible to evidence an encouraging scenario after evaluating the responses to the second questionnaire. However, favoring prior knowledge about microorganisms and their benefits is undoubtedly essential in the construction of knowledge about what is true.